Determination of the factors affecting the frequency and of chemotherapyinduced alopecia and methods of coping with alopecia - KOLAÇ, NURCAN (My University, 2022)
Objective: The aim of this cross-sectional descriptive study is to determine the chemotherapy-induced alopecia and the patients’ coping methods with alopecia. Materials and Methods: This descriptive study was conducted with 240 patients who applied to chemotherapy unit of two private hospitals in Istanbul between December 2019 and January 2020. The data were collected using a patient information form developed by the researchers upon the literature review. Results: It was determined that 85.7% of the women experienced alopecia problem and the difference was significant according to their gender (p=0.00). Ninety two percent of patients with genitourinary system cancer and 88.5% of breast cancer patients experienced alopecia, the difference was statistically significant, and the significance was caused by experiencing alopecia more in these cancer types than the other cancer types (p=0.007). It was determined that 82.5% of the patients, who were receiving chemotherapy for less than a year, statistically significantly experienced alopecia more compared to the patients who were receiving chemotherapy for a longer period (p=0.031). It was also found that 69.7% of patients with Stage IV cancer experienced alopecia but they experienced alopecia statistically significantly less compared to the other stage patients (p=0.040). When the patients were examined in terms of diagnosis time according to family history of breast cancer, it was determined that 43.6% of those, who had family history of breast cancer, and 63.8% of those, who had no family history of breast cancer, were diagnosed in the stage II of their disease. The distribution of the cancer diagnosis time of patients according to having breast cancer history in the family was statistically significant (p=0.000). It was determined that 28.2% of the patients who had family history of breast cancer and 21.0% of the patients, who had no family history of breast cancer, noticed the lump for the first time in their regular self-breast examination. The distribution of duration of cancer diagnosis based on family history of breast cancer and the way of noticing the lump in the breast were statistically significant (p=0.000, p=0.014). It was also determined that 61.0% of the patients experiencing alopecia used a wig-bonnet (p=0.00) and there was no statistically significant difference between experiencing alopecia and age, marital status, occupation, place of residence, income status and social security. Conclusion: Alopecia was seen to be more common in women. Patients with genito-urinary system and breast cancer experienced alopecia more than other cancer patients. More than half of the women used bonnets and wigs. As the education level increased, women’s status of using bonnet and wig increased as well.

Amaç: Kemoterapiye bağlı saç dökülmesinin sıklığı ve hastaların saç dökülmesi ile baş etme yöntemlerinin belirlenmesidir. Gereç ve Yöntemler: Araştırma, Aralık 2019-Ocak 2020 tarihleri arasında İstanbul’da iki özel hastanenin kemoterapi ünitesine başvuran 240 hasta ile tanımlayıcı olarak yapıldı. Veriler; araştırmacılar tarafından literatür doğrultusunda geliştirilen hasta bilgi formu ile toplandı. Bulgular: Kadınların %85.7’sinin saçlarda dökülme sorunu yaşadıkları farkın cinsiyetlerine göre anlamlı olduğu belirlenmiştir (p=0.00). Genitoüriner sistem kanseri hastalarının %92.0’ının meme kanseri hastalarının %88.5’inin saçlarda dökülme sorunu yaşadıkları, farkın istatistiksel olarak anlamlı olduğu, anlamlılığın bu kanser türlerinde saç dökülme sorununun diğer kanser türlerine göre daha fazla yaşanmasından kaynaklandığı saptanmıştır (p=0.007). Bir yıldan az süredir kemoterapi alanların %82.5’inin, daha uzun süredir kemoterapi alan hastalara göre istatistiksel olarak anlamlı olacak şekilde saçlarda dökülme sorununu daha fazla yaşadıkları belirlenmiştir (p=0.031). Evre IV kanser hastalarının %69.7’sinin saçlarda dökülme sorunu yaşadıkları diğer evre hastalarına göre istatistiksel olarak anlamlı olacak şekilde saçlarda dökülme sorununu daha az yaşadıkları belirlenmiştir (p=0.040). Hastalar ailesine meme kanseri öyküsüne göre tanı zamanı açısından incelendiğinde, ailesinde meme kanseri öyküsü olanların %43.6'sının, ailesinde meme kanseri öyküsü olmayanlarınsa %63.8'inin hastalığın II. evresinde teşhis konuluğu belirlendi. Hastaların kanser tanı zamanlarının dağılımı ailede meme kanseri öyküsü olup olmamasına göre istatistiksel olarak anlamlıydı (p=0.000). Ailesinde meme kanseri öyküsü olanların %28.2'sinin, ailesinde meme kanseri öyküsü olmayan hastaların %21.0'i kitleyi ilk kez kendi meme muayenelinde fark etmiştir. Ailede meme kanseri öyküsüne göre kanser tanı süresinin dağılımı ve memedeki kitleyi fark etme şekli istatistiksel olarak anlamlıydı (p=0.000, p=0.014). Saçlarda dökülme sorunu yaşayan hastaların %61.0’ının peruk-bone kullandığı (p=0.00), saçlarda dökülme sorunu yaşama ile yaş, medeni durum, meslek, yaşanılan yer, gelir durumu, sosyal güvence olma durumları arasında istatistiksel olarak anlamlı farklılık olmadığı belirlenmiştir. Sonuç: Alopesi kadınlarda daha fazla görülmüştür. Saç dökülmesini genitoürüner sistem ve meme kanseri olan hastalar diğer kanser hastalarına göre daha fazla yaşamışlardır. Kadınların yarısından fazlası bone ve peruk kullanmıştır. Eğitim düzeyi arttıkça kadınların bone ve peruk kullanma durumları artmıştır.
Kemoterapiye bağlı alopesi sıklığı ve hastaların baş etme yöntemleri
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Alopecia; Cancer; Chemotherapy; Coping strategies; Gender; Alopesi; Baş etme stratejileri; Cinsiyet; Kanser; Kemoterapi